Differential expression of nuclear hormone receptors by dendritic cell subsets in human vaginal mucosa and skin - Joo, HyeMee; Gu, Chao; Wiest, Matthew; Duluc, Dorothee; Fernandez, Emyly; Nyarige, Verah; Yi, Johnny; Oh, SangKon (Frontiers in Immunology, 2023)
Nuclear hormone receptors (NHRs) expressed by dendritic cells (DCs), the major immune inducers and regulators, could play important roles in host immunity. Assessment of NHRs expressed by DCs in the vaginal mucosa (VM), in comparison with those expressed by DCs in other tissues, will thus help us understand the immunology of human vagina. This study identified 16 NHR transcripts that are differentially expressed among 8 different antigen presenting cell (APC) subsets isolated from human VM, skin, and blood. The expression profiles of NHRs were largely tissue specific. VM APCs expressed increased levels of LXRA, RXRA, ESRRA, ESRRAP2, and PPARG, whereas skin and blood APCs expressed increased levels of NURR1, NOR1 and RARA. Of interest, female sex hormone receptors, ESR1 and PGR, were found to be mainly expressed by non-APC cell types in the VM; ESR1 by HLA-DR+CD34+ and PGR by HLA-DR- cells. ERα and PR were expressed by vimentin+ cells in the VM, but not in human skin. ERα, but not PR, was also expressed in CD10+ cells in the lamina propria of VM. In conclusion, NHR expression by APC subsets is tissue- and cell type-specific. Future studies on the roles of individual NHRs expressed by different cell types, including DC subsets, in the human VM are warranted.